A Preliminary Study: Comparison of Pain Intensity of Intratympanic Steroid Injection between Using 10% Lidocaine Spray 10 and 20 Minutes: Lidocaine Spray 10 or 20 minutes for IT injection - วิริยา แสงเจริญ พ.บ., สุวิชา แก้วศิริอิศราดิสัยกุล พ.บ., จารึก หาญประเสริฐพงษ์ พ.บ. , ศณัฐธร เชาวน์ศิลป์ พ.บ., ภาสกร สวัสดิรักษ์พ.บ. (Thai Journal of Otolaryngology Head and Neck Surgery, 2022)
Objectives: Comparison between using 10% Lidocaine spray 10 and 20 minutes for intratympanic steroid injection in idiopathic sudden sensorineural hearing loss Materials and methods: Randomized controlled trial, parallel trial Results : There were 32 patients. The p-values between two groups of total 11-point numeric rating scales (NRS-11) between two groups 1) after suction the lidocaine =0.61, 2) during needle insertion at tympanic membrane =0.86, 3) at 30 minutes after suction =0.04. The patient’s satisfaction was in good to excellent level 81%. The p-values of side effects between two group s= 0.39 Conclusion : No difference of pain intensity after suction and during needle insertion, satisfaction, and side effect between the two groups. Keyword : intratympanic steroid injection, local anesthesia, lidocaine, pain intensity